Asenapine versus olanzapine for the treatment of nausea and vomiting in patients with cancer: A retrospective study - Tomohiko Kimura; Akifumi Kanai; Hiroyuki Muraoka; Yuichiro Takahashi; Masatomo Ara; Ken Inada (Wiley, 2024)
Abstract Aim Patients with cancer often experience nausea and vomiting (N/V), but may have difficulty using olanzapine (OLZ), a common antiemetic. Asenapine (ASE) is a multi‐acting receptor‐targeted antipsychotic like OLZ, although there is little evidence that ASE serves as an antiemetic. The aim of this study was to evaluate the efficacy and tolerability of ASE compared to those of OLZ for the treatment of N/V in patients with cancer. Methods This retrospective study involved patients who received 5 mg ASE, 5 mg OLZ, or 2.5 mg OLZ for 2 days. Daily worst N/V was rated on a scale of 0 (none) to 3 (very much). The primary endpoint was the proportion of patients who had a response, defined as any reduction in N/V score. A complete response (CR) was defined as a score reduction to 0. Secondary endpoints included the proportion of patients with CR and adverse events. Results Between April 2017 and March 2023, 212 patients were enrolled to receive treatment: 5 mg ASE (n = 34), 5 mg OLZ (n = 102), or 2.5 mg OLZ (n = 76). No significant differences in response rates (52.9% vs. 58.8% vs. 52.6%, p = 0.671) or secondary endpoints were observed between the groups. Patients receiving ASE were more likely to experience oral hypoesthesia (p = 0.004). Conclusion This preliminary study suggests that ASE may be effective for N/V. Further studies are required to confirm these findings.